Harmful mesostigmatic mites ectoparasitic to honey bees - Emmanouel, N.G.; Pelekassis, C.D.; Santas, L.A. (ENTOMOLOGIA HELLENICA, 1983)
Mites of the order Mesostigmata are among the frequent and dominant components of the beehive acarofauna. Several of them belonging to the families: Varroidae. Laelapidae and Ameroseiidae are important parasites or capably harmful species to the honey bee. Among them, V. jacobsoni and Neocypholaelaps favus are widespread in Greece, while the existence of a third species Mellitiphis alvearius is quite probable. A brief treatise of the harmful mesostigmatic mites found in the beehives all over the world is given. Detailed drawings of all stages of V. jacobsoni are given, of which drawings the immature stages appear for the first time.